Process-dependent ferroelectric and memristive properties in polycrystalline Ca:HfO2-based devices - Ferreyra, C.; Badillo, M.; Sánchez, M. J.; Acuautla, M.; Noheda, B.; Rubi, D. (Frontiers in Materials, 2025)
Memristors are considered key building blocks for developing neuromorphic or in-memory computing hardware. Here, we study the ferroelectric and memristive response of Pt/Ca:HfO2/Pt devices fabricated on silicon by spin-coating from chemical solution deposition followed by a pyrolysis step and a final thermal treatment for crystallization at 800°C for 90 s. For pyrolysis temperature of 300°C, the annealed samples are ferroelectric while for 400°C a dielectric behavior is observed. For each case, we found a distinct, forming-free, memristive response. Ferroelectric devices can sustain polarization switching and memristive behavior simultaneously. Aided by numerical simulations, we describe the memristive behavior of ferroelectric devices arising from oxide-metal Schottky barriers modulation by both the direction of the electrical polarization and oxygen vacancy electromigration. For non-ferroelectric samples, only the latter effect controls the memristive behavior.